Hiring & Managing A Millennial Workforce - Charest, Trudi (Canadian Journal of Optometry, 2018)
The average Canadian Optometry practice is shifting. Millennial employees are quickly becoming the majority of staff in an Optometry practice. Millennials change careers more than any other previous generation so becoming a better recruiter will be a crucial business skill as you will be hiring more frequently than before.